Scorpion venom phospholipases A2: A minireview. (September 2020) - Krayem, Najeh; Gargouri, Youssef
Abstract: Many venomous species, including snakes, bees and scorpions, contain a variety of secreted phospholipases A2 (sPLA2 ) that contribute to prey digestion and venom toxicity. Based on their primary structures, the different venom sPLA2 have been classified into four groups I, II, III and IX. While the structure of sPLA2 groups II and I has been well characterized, only one crystal structure of group III sPLA2 from bee venom was described. Scorpion venom sPLA2 belong to group III with a particular heterodimeric structure composed of a long enzymatic chain linked by a disulfide bridge to a Short one after the release of five residues (penta-peptide) during the maturation processes. The function of the Short chain is still not clear. Its sequence varies in composition and in length between different scorpion species . Available studies of the structure-function relationships of scorpion venom sPLA2 are limited. Some biological activities of these enzymes such as neurotoxicity, myotoxicity, along with the hemolytic, anticoagulant, anti-tumoral and anti-angiogenic activities have been investigated. In this review, we tentatively summarize the last findings about the biochemical properties, the structure-function relation and the biological activities of scorpion venom phospholipases A2 . In addition to expanding the database of structures for these sPLA2 and understanding their properties and functions, this survey is intended to explore the molecular mechanisms and signaling pathways of the described biological activities.